Postmodernism and China - Abidin, Kusno; Anthony, King; Arif, Dirlik; Chao, Liao; Chen, Xiaoming; Dai, Jinhua; Dirlik, Arif; Jeroen, Kloet; Liu, Kang; Ping, Liao; Sebastian, Liao; Sheldon, Lu; et al. (Duke University Press, 2000)
Few countries have been so transformed in recent decades as China. With a dynamically growing economy and a rapidly changing social structure, China challenges the West to understand the nature of its modernization. Using postmodernism as both a global frame of periodization and a way to break free from the rigid ideology of westernization as modernity, this volume's diverse group of contributors argues that the Chinese experience is crucial for understanding postmodernism.Collectively, these essays question the implications of specific phenomena, like literature, architecture, rock music, and film, in a postsocialist society. Some essays address China's complicity in-as well as its resistance to-the culture of global capitalism. Others evaluate the impact of efforts to redefine national culture in terms of enhanced freedoms and expressions of the imagination in everyday life.